Compromised Cerebrovascular Regulation and Cerebral Oxygenation in Pulmonary Arterial Hypertension. Issue 10 (12th October 2017) - Malenfant, Simon; Brassard, Patrice; Paquette, Myriam; Le Blanc, Olivier; Chouinard, Audrey; Nadeau, Valérie; Allan, Philip D.; Tzeng, Yu‐Chieh; Simard, Sébastien; Bonnet, Sébastien; Provencher, Steeve
Abstract : Background: Functional cerebrovascular regulatory mechanisms are important for maintaining constant cerebral blood flow and oxygen supply in heathy individuals and are altered in heart failure. We aim to examine whether pulmonary arterial hypertension (PAH) is associated with abnormal cerebrovascular regulation and lower cerebral oxygenation and their physiological and clinical consequences. Methods and Results: Resting mean flow velocity in the middle cerebral artery mean flow velocity in the middle cerebral artery (MCAvmean ); transcranial Doppler), cerebral pressure‐flow relationship (assessed at rest and during squat‐stand maneuvers; analyzed using transfer function analysis), cerebrovascular reactivity to CO2, and central chemoreflex were assessed in 11 patients with PAH and 11 matched healthy controls. Both groups also completed an incremental ramp exercise protocol until exhaustion, during which MCAvmean, mean arterial pressure, cardiac output (photoplethysmography), end‐tidal partial pressure of CO2, and cerebral oxygenation (near‐infrared spectroscopy) were measured. Patients were characterized by a significant decrease in resting MCAvmean ( P <0.01) and higher transfer function gain at rest and during squat‐stand maneuvers (both P <0.05). Cerebrovascular reactivity to CO2 was reduced ( P =0.03), whereas central chemoreceptor sensitivity was increased in PAH ( P <0.01), the latter correlating with increased resting ventilation ( R 2 =0.47; P <0.05) and the exercise ventilation/CO2 production slope ( V ˙ E / V ˙ CO 2 slope; R 2 =0.62; P <0.05) during exercise for patients. Exercise‐induced increases in MCAvmean were limited in PAH ( P <0.05). Reduced MCAvmean contributed to impaired cerebral oxygen delivery and oxygenation (both P <0.05), the latter correlating with exercise capacity in patients with PAH ( R 2 =0.52; P =0.01). Conclusions: These findings provide comprehensive evidence for physiologically and clinically relevant impairments in cerebral hemodynamic regulation and oxygenation in PAH.